Actual online shopping behavior among Jordanian customers - A. Al- Jabari, Mohammed; Othman, Siti Norezam; Nik Mat, Nik Kamariah (Scientific & Academic Publishing Co., 2012)
Internet technology is becoming increasingly important in our daily life in general and in business world particularly.This increased role of the Internet encourages the researchers to investigate the customer behavior in this emerging market. The aim of this study is to examine the factors that give rise to the formation of the actual online shopping behavior of Jordanian customers.The study analyses the predictor variables of planned behavior among 313 university academic staff selected on the basis of probability sampling.Structural equation modeling (SEM) was used to analyze the causal relationships in accordance with the theory of planned behavior (TPB).The findings depicted that subjective norm and perceived behavioral control to have significant positive effects on intention. Attitude has no direct significant impact on online shopping intention.Online shopping intention also has a positive and significant impact on actual online shopping behavior.The practical implication of the research is discussed